Differential T-cell responses in dogs with meningoencephalomyelitis of unknown origin compared to healthy controls - Barber, Renee; Barber, James (Frontiers in Veterinary Science, 2022)
Meningoencephalomyelitis of unknown origin (MUO) is a common disorder in dogs that results in mononuclear inflammation in the brain and/or spinal cord. MUO is presumed to be autoimmune but specific immunological aberrations have not been identified. This exploratory study aimed to evaluate T cell production of two cytokines commonly implicated in autoimmune disease, interferon-gamma (IFNg) and interleukin-17 (IL17). Peripheral blood mononuclear cells were obtained from 12 dogs with MUO and 10 healthy controls, stimulated to activate intracellular signaling pathways, and stained with a cluster of differentiation 4 (CD4), cluster of differentiation eight (CD8), IFNg, and IL17 antibodies prior to analysis by flow cytometry. Mean differences in absolute cell numbers are represented as MUO cases minus healthy controls, and 95% Cis are reported. Overall IFNg-producing lymphocytes (mean difference = 241.8 cells/ul, 95% CI = 65.6 to 418.1) and CD4+ IFNg-producing T-cells (mean difference = 188.4, 95% CI = 77.3 to 299.5) were fewer in MUO cases. Additionally, CD4+ IL17-producing T-cells were greater in MUO cases (mean difference −34.9, 95% CI = −50.54 to −19.17) and CD8+ IL17-producing T-cells were fewer in MUO cases (mean difference = 73.5, 95% CI = 6.8 to 140.1). These results support that immunological changes can be identified in peripheral blood cells of dogs with MUO and suggest that T-helper type 17 (Th17) cells may play a role in pathogenesis.